A DEEP SEISMIC TRANSECT FROM HOVGåRD RIDGE TO NORTHWESTERN SVALBARD ACROSS THE CONTINENTAL-OCEAN TRANSITION: A SHEARED MARGIN STUDY - Ritzmann O.; Jokat W.; Czuba W.; Guterch A.; Mjelde R.; Nishimura Y. (My University, 2004)
New seismic refraction data were collected across the western Svalbard continental marginoff Kongsfjorden (Ny ?lesund) during the cruise leg ARK15/2 of RV Polarstern. The use ofon- and offshore seismic receivers and a dense airgun shot pattern provide a detailed viewof the velocity structure of SvalbardOs continental interior, the continent-ocean transition,and oceanic crust related to the northern Knipovich Ridge and the Molloy Ridge.The Caledonian central and western terranes of Svalbard are not distinguishable on the basisof seismic velocity structure. Below a 7 to 8 km thick Paleozoic sedimentary cover the crystallinecrust reveals a three-layer structure with seismic velocities ranging between 6.1 and 6.9 km/s.The geological suture between the terranes is imperceptible. The middle and upper crust belowthe Tertiary Forlandsundet Graben shows striking low velocities. This can be related to theEarly Paleozoic convergent transpressive movements between Svalbard and northern Greenland,followed by an extensional (relaxing) phase. We argue that a brittle-fractured rock formation ispresent below the graben, which also buries a sedimentary Paleozoic core.The continent-ocean transition can be classified as a sheared margin formed at the continentalpart of the Spitsbergen Fracture Zone. Moderate crustal thinning is achieved only to the westof the low velocity zone below the Forlandsundet Graben. This leads to the assumption thattranstensional rift movements since Oligocene were decoupled from the central terraneof Svalbard. The Moho dips with an angle of 45° eastwards at the continent-ocean transitionthat exhibits higher seismic velocities of 7.2 km/s on the continental side. These can beinterpreted as minor mantle-derived intrusions, probably induced by convection due to thejuxtaposition of cool continental and hot oceanic lithosphere.The oceanic crust generated at the Knipovich Ridge and the Molloy Ridge is thin (2 to 4 km),compared to the global mean, and is characterised by the absence of oceanic layer 3. Theseobservations can be ascribed to conductive cooling of the ascending mantle due to theextremely low divergence rate and the neighbouring cool continental crust. The underlyingmantle is slightly serpentinized below the Knipovich Ridge segment, reflected by low seismicvelocities of ~7.7 km/s. A thicker sequence of syn- and post rift sediments and sedimentaryrocks are observed on the Molloy Ridge oceanic segment, which results from greater subsidencerelative to the Knipovich Ridge segment.
Keywords: continental margins; crustal structure; fracture zone; refraction seismology; Svalbard